MALAY VERSION OF THE MOTIVATED STRATEGIES FOR LEARNING QUESTIONNAIRE (MSLQ) - Nor Rashidah Paujah @ Ismail; Fadzilah Abdol Razak; Norhasliza Ahmad (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
Motivation plays a crucial role in the academic success of students, particularly in challenging courses like Statistics. In an effort to measure students’ motivation in studying statistics courses, a study was developed based on the Motivated Strategies for Learning Questionnaire (MSLQ). The study focused on creating a translated version of the original questionnaire in Malay language to assess student motivation. An early analysis was conducted starting with Exploratory Factor Analysis to evaluate whether the translated instrument measured the motivational level as effectively as the original version of MSLQ. Following the factor analysis, the reliability analysis was performed to determine the reliability of the translated questionnaire. The results indicated that the translated instrument is a reliable measure of student motivation in studying statistics courses and supported the original version of MSLQ. However, there were some differences in the factor structure of the questionnaire, with certain items not being grouped in the same component as in the original version. These differences were attributed to language factors and differences in the educational environment. It is worth noting that the MSLQ has been extensively validated in various languages and educational settings and has been found to be a reliable and valid measure of student motivation in various subjects. By translating the MSLQ into Malay language, the researchers have contributed to the growing body of research on student motivation in Malaysia, which could potentially enlighten interventions and strategies to improve student outcomes in this region.